Use of the Internet as an Online Learning Media - Mufron, Ali; Jie, Lie; Jixiong, Cai; Wei, Zhang; Xu, Shanshan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The use of online media is the easiest way to use nowadays, access is easy to reach wherever you are. Online media can be accessed by every group, especially in the world of education. In this increasingly hot era of globalization, educators are required to be more creative and innovative in using online media. Online media is media in which there are millions of pieces of knowledge which are very useful for educators and students in gaining knowledge. There are online media that can be accessed by educators and students, such as: goggle, e-book goggle scholar. The objectives of the research include 1) To make it easier for students to access the material 2) To find information about the material 3) To teach students about technological advances 4) To make students aware of world developments quickly. The method used in this research is a quantitative method which is carried out by means of an online-based survey. The results of this research are how the use of online media in the world of education can increase students' enthusiasm in gaining knowledge, make students not feel bored in the learning process, help educators in finding material to be taught to students. The researcher's conclusion about online media is that it is very helpful in finding the knowledge that educators and students need, making it easier to access learning. The limitation of this research is that the researcher does not know whether the educator participants are really using online media to find material only, the researcher hopes that future researchers will make further observations regarding online media.